Translanguaging in Higher Education - Silwal, Tanka (Studies in ELT and Applied Linguistics, 2021)
Teachers’ pedagogical practices have vital role to cater the students’ achievement in education in general and in language (here English) education in particular. This study aims to explore English language teachers’ pedagogical practices with special reference to translanguaging. I employed qualitative research design for the study. The participants of the study were four community college teachers and six students of Dhading district. For the collection of the data, I observed four classes of each teacher; interviewed with the same teachers; and organized focus group discussion with the students. The findings were discussed under eight headings thematically. The conclusion of findings indicates that translanguaging can be a useful pedagogy even in the higher education. Hence, it has been recommended that the English language practitioners can conduct large scale studies on the relevance of translanguagins in higher education.